2019
DOI: 10.3390/ijms20143563
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of GDF11: Myth or Reality?

Abstract: In the brain, aging is accompanied by cellular and functional deficiencies that promote vulnerability to neurodegenerative disorders. In blood plasma from young and old animals, various factors such as growth differentiation factor 11 (GDF11), whose levels are elevated in young animals, have been identified. The blood concentrations of these factors appear to be inversely correlated with the age-related decline of neurogenesis. The identification of GDF11 as a “rejuvenating factor” opens up perspectives for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…(2) The GDF11 enhanced by LIPUS did not show any function on the brain aging. However, it was contradicting with previous reports [43,44]. The relationship between the effect of GDF11 and aging process awaits further investigation.…”
Section: Discussioncontrasting
confidence: 64%
“…(2) The GDF11 enhanced by LIPUS did not show any function on the brain aging. However, it was contradicting with previous reports [43,44]. The relationship between the effect of GDF11 and aging process awaits further investigation.…”
Section: Discussioncontrasting
confidence: 64%
“…It is widely expressed in adult CNS and has a crucial impact on brain development (11). Previous study has shown that GDF-11 can enhance neurogenesis in the brain, especially in the hippocampus, helping remodeling the synapses and repairing the injured neurons (15,29,30). It can also regulate the function of astrocytes, whose activation are shown to contribute to the pathogenesis of schizophrenia (11).…”
Section: Discussionmentioning
confidence: 99%
“…Because GDF11 is highly expressed in the brain and potentially neuroprotective [7], we used The Cancer Genome Atlas (TCGA) to assess the effect of GDF11 expression in malignant gliomas.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%